Serum uric acid as a metabolic regulator of endothelial function in heart failure - Alexander E Berezin (Archives of Clinical Hypertension - Peertechz Publications, 2017)
The development of heart failure (HF) associated with elevated level of serum uric acid (SUA).Additionally, the majority of individuals with traditional cardiovascular risk factors contributing in HF risk exhibited increased levels of SUA. Although SUA lowering drugs are widely used in patients with symptomatic hyperuricemia and gout beyond their etiologies, there is no agreement of SUA below target level 6.0 mg/dL in asymptomatic individuals with kidney injury and CV disease and data of ones in heart failure (HF) are suffi ciently controversial. First SUA plays an important role in inducing oxidative stress, infl ammation, neurohumoral activation, and endothelial dysfunction. Secondary, SUA may act as antioxidant contributing in restoring of vascular function. Moreover, SUA is able to epigenetically regulate a survival of endothelial precursors, mediate their mobbing and differentiation, as well as coordinate a turn-over effect of metabolic memory phenomenon into repair capability of cell precursors. However, elevated SUA level was found a predictor of adverse clinical outcomes of HF. The short communication is depicted the importance of new clinical data to confi rm the emerging reparative ability of SUA in HF and its role as  romising target for treatment in cardiac failure.